2021
DOI: 10.1007/s42832-021-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation methods of heavy metal pollution in soils based on enzyme activities: A review

Abstract: Soil enzyme activities have been suggested as suitable indicators for the evaluation of metal contamination because they are susceptible to microbial changes caused by heavy metal stress and are strictly related to soil nutrient cycles. However, there is a growing lack of recognition and summary of the historic advancements that use soil enzymology as the proposal of evaluation methods. Here, we review the most common methods of heavy metal pollution evaluation based on enzyme activities, which include single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…According to Ghori et al (2019), plants markedly increase root exudate production in response to a contaminated environment. This subsequently increased the activity of the microorganisms, which then released more β-glucosidase for glucose hydrolysis (Cui et al 2021). Similarly, Duan et al (2022), who studied the activity of soil enzymes in the root zone of Medicago sativa growing in soils contaminated with Cd, Pb, Zn, and Cu, observed a significant increasing trend.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…According to Ghori et al (2019), plants markedly increase root exudate production in response to a contaminated environment. This subsequently increased the activity of the microorganisms, which then released more β-glucosidase for glucose hydrolysis (Cui et al 2021). Similarly, Duan et al (2022), who studied the activity of soil enzymes in the root zone of Medicago sativa growing in soils contaminated with Cd, Pb, Zn, and Cu, observed a significant increasing trend.…”
Section: Resultsmentioning
confidence: 92%
“…The accumulation of toxic elements by plants results in entry into the food chain, which then becomes hazardous to human health (Pande et al 2022).Soil enzymes produced extracellularly by microorganisms are key participants in soil nutrient cycles and functional sustainability. They are sensitive to changes in the soil environment, such as contamination by toxic elements (Wahsha et al 2017, Nkongolo and Narendrula-Kotha 2020, Cui et al 2021, Majumder et al 2022. Due to these characteristics, they can be used as biological indicators for evaluating soil health (Aponte et al 2020b, Skowrońska et al 2020.The mineralisation of carbon (C) in the soil is crucial for soil quality, as it increases soil fertility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The soil P mineralization-immobilization dynamics are dominated by microbial activities and phosphatase secreted by microorganisms and plants (Oehl et al, 2001;Margalef et al, 2021). At present, there is no consistent conclusion about the effects of Cd on phosphatase (Cui et al, 2021). Quiquampoix and Mousain (2005) and Yang et al (2016) reported Cd stimulates phosphatase activity, whereas some researchers observed the inhibiting effect of Cd (Pan and Yu, 2011;Xian et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Soil degradation is without a doubt one of the world's most pressing environmental issues. As a result of various degradation processes around the world (Ranjani et al, 2021), approximately 6 million hectares of farming fields have become less productive (Cui et al, 2021). For example, the value of Iraqi sediment plains land is decreasing due to a rise in the number of companies and their pollution, urbanization, increasing traffic levels, and even the exploitation of sewage and waste dumps (Bahram et al, 2018).…”
Section: Introductionmentioning
confidence: 99%